Placing the Commoning First: Getting Beyond the Patronage Trap in Natural Resource Decentralization Policies - Sirimorok, Nurhady; Fisher, Micah R.; Verheijen, Bart; Sahide, Muhammad Alif K. (Forestry Faculty, Universitas Hasanuddin, 2023)
Research on the commons have been an inspiration for initiatives on natural resource decentralization over the past three decades. Researchers are increasingly recognizing however, that these commons initiatives are mostly failing to support rights, improve livelihoods, and conserve natural resources. These “commons projects,” defined as approaches that claim to devolve natural resource governance to local institutions, have their origins in various formulations of theories of the commons but are usually interpreted and applied by states and donor organizations. This paper identifies and analyzes deficiencies in theories of the commons through the slight but significant refocusing on perspectives of commoning. We found that commons scholarship lacks a grounding in power relations, and furthermore, tends to portray commons-governing groups as homogenous communities enacting long-established practices. Conversely, a commoning perspective provides a more dynamic and relational approach, and thus distinctly centers political dimensions of collective practices among diverse groups of citizens. We also extend this argument by showing that a fundamental shift in understanding commoning will help advocate for, and anticipate what commoners can actually do in regions of the Global South undergoing widespread enclosures in the face of powerful informal patronage networks controlled by state power actors and interests.